Dissipative Dynamics of Quantum and Classical Correlations for Two-Qubit Under Two-Side and One-Side Decoherence (Journal of Atomic and Molecular Sciences, 2021)
The dissipative dynamics of classical correlation(CC), quantum discord(QD) and entanglement (QE) of two qubits in two-side and one-side decoherence models are investigated under Markovian environments. We find the sudden change QD as well as CC and sudden death of entanglement (ESD). The results show that QD and QE decay faster with the increasing of squeezing parameter $r;$ the dipole-dipole interaction $Ω$ under two-side decoherence leads to the oscillation of quantum discord and concurrence for initial non-eigenstates; while in all cases when entanglement suddenly disappears, quantum discord keeps nonzero under same conditions.